Exploring the implementation of integrated reporting: a comparative literature review across countries - Shanmugam, Jaya Kumar; Che Adenan, Nur Zharifah; Jamaludin, Mohd Faizal; Hamid, Muhammad Hariz; Mohd Jamil, Muslimah (GADING Journal for the Social Sciences, 2025)
Corporate reporting has historically focused on financial disclosures, frequently neglecting essential non-financial elements like Environmental, Social, and Governance (ESG) factors, resulting in issues regarding transparency, accountability, and stakeholder choices. Integrated Reporting (IR) has arisen to fill this gap by offering a comprehensive perspective on an organisation‘s value-creation process. Nonetheless, the adoption of IR differs among countries due to varying regulatory frameworks, levels of institutional support, and corporate governance systems. This research examines the global application of IR, pinpointing essential motivators, obstacles, and effective strategies. Employing a comparative literature review approach, the research thoroughly examined peer-reviewed articles, regulatory documents, and industry reports from 2018 to 2024, utilising thematic analysis and cross-national comparisons. The results indicate that compulsory regulatory structures in Europe and South Africa have greatly influenced IR adoption, while voluntary adoption in Malaysia, Sri Lanka, and Nigeria has caused variable reporting practices. Major difficulties consist of elevated compliance expenses, insufficient expertise, and poor regulatory enforcement, especially in developing countries. Despite these challenges, worldwide trends suggest a move towards standardisation, technology-enabled reporting, and improved stakeholder involvement. The research highlights the necessity of aligning regulations and enhancing capabilities to promote wider adoption of IR. Policymakers and businesses need to synchronise IR frameworks with sustainability objectives to enhance corporate transparency and foster long-term value creation. Future studies ought to examine digital advancements and sector-specific IR applications to enhance corporate reporting and facilitate informed decision-making for stakeholders.